The Cruel Prince - Book 1 - Black, Holly (New York : Little, Brown and Company, 2018)
Jude, seventeen and mortal, gets tangled in palace intrigues while trying to win a place in the treacherous High Court of Faerie, where she and her sisters have lived for a decade.
Accelerated Reader AR